Study of parking demand and supply in U.P. Diliman - Espiritu, Andrea M.; Gungon, Maria Paulina E.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Organized parking schemes are necessary in every establishment. Parking has not been considered a problem in UP Diliman based from the study made by the NCTS in 2008. However, a significant indicator of the lack of off-street parking facilities in the campus is the propensity for on-street parking as vehicles tend to park at any available space within the campus. This study aims to characterize the general parking conditions, estimate the current parking supply and demand and recommend improvement in parking situations in an area within UP Diliman. In order to carry out the objectives of this study, selection of study area and other suitable parameters was undertaken. The study area comprises of the College of Engineering, National Engineering Center and College of Law. Various methods in characterizing parking conditions such as parking inventory survey and parking demand survey were conducted. Based from the results, current parking supply was found to be generally less than the current parking demand. Occupancy rates of on-street parking areas were higher compared to the off-street parking facilities. Such case was visible in the College of Engineering and College of Law. This indicates that off-street parking facilities are not utilized as they are restricted to faculty and staff use only. Requirements for the number of parking spaces per building were measured using ITE's parking generation rate and minimum requirement from the National Building Code (NBC, 2004) of the Philippines. Although the current parking supply meets the requirements of NBC, it is not sufficient for the current parking demand. The requirement by the NBC is just a minimum requirement and does not reflect the actual demand for parking. Meanwhile, the current parking supply is very low compared to the estimated parking spaces required from the ITE parking generation rate. This is due to the parking generation rate being formulated from international (U.S.) conditions which may not be practical to use at local conditions. Thus, an effort to produce a parking generation rate formulated from local conditions was made but the rate estimated was relatively low in part due to a lack of data points to obtain a better regression model. It is recommended to replicate the study to other areas of the campus to obtain more data points and produce a more precise local parking generation rate. To alleviate the problems in parking, a concrete parking management system must be established. This system will be responsible for the inspection of roads and parking facilities and proper designation of parking areas. Also, promotion on vehicle reduction in the campus must be done by encouraging the students on alternative modes of transportation such walking and biking.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Campus parking; University of the Philippines -- Parking; Automobile parking